Technique and Device to Evaluate Lightning Air Terminal Collection Volume - Zainuddin Nawawi; Hussein Ahmad; Muhammad Abu Bakar Sidik; Lim Pai Hung; Aulia .; Hamizah Shahroom; Muhammad ‘Irfan Jambak (Proceeding of the Electrical Engineering Computer Science and Informatics, 2014)
Lightning air terminals are a very significant part of lightning protection system (LPS) for buildings, structures and facilities. With reference to the facilities requiring lightning protection the position, the apparent height, and the angle of protection of lightning air terminals determines the collection volume (CV) of the protected area. The CV of direct strike lightning air terminals can change due to facilities which are affected by natural disasters such as seismic tremor and flood. If such natural disasters do happen, there are possibilities that the facilities will not be fully protected from direct lightning strikes due to building and structure misalignment the aftermath of seismic tremor and flood related earth movement. So for the safety of equipment and personnel, lightning protection system efficacy assurance is necessary. Therefore, there should be a technique and device to monitor the variation of collection volume afforded by every lightning air terminal on buildings and structures after the occurrence of a natural disaster. This paper presents a new technique as well as a new device to monitor the collection volume variation. A part of the device was obtained from a recycled moveable television antenna. This approach is not only practical, portable and cost effective but also incorporating the idea of environmental protection and recycling of used plastic materials.